Tailoring of Gradient Particles of Li-Rich Layered Cathodes with Mitigated Voltage Decay for Lithium-Ion Batteries - Ju, Xiaokang; Hou, Xu ; 0000-0003-0398-2006; Beuse, Thomas; Liu, Zhongqing; Du, Leilei; Brinkmann, Jan-Paul; Paillard, Elie; Wang, Taihong; Winter, Martin; Li, Jie (ACS Applied Materials and Interfaces, 2020)
Voltage decay during cycling is still a major issue for Li-rich cathodes in lithium ion batteries. Recently, the increase of Ni content has been recognized as an effective way to mitigate this problem, although it leads to lower-capacity materials. To find a balance between voltage decay and high capacity, particles of Li-rich materials with concentration gradients of transition metals have been prepared. Since voltage decay is caused by oxygen loss and phase transition that occur mainly on the particle surface, the Ni content is designed with a negative gradient of concentration from the surface to the bulk of particles. To do so, microsized Li1.20Ni0.13Co0.13Mn0.54O2 particles are mixed with much smaller LiNi0.8Co0.1Mn0.1O2 particles to form deposits of small particles onto larger particles. The concentration gradient of Ni is achieved as the Ni ions in LiNi0.8Co0.1Mn0.1O2 penetrate into Li1.20Ni0.13Co0.13Mn0.54O2 during a calcination post-treatment. Gradient samples show superior cycling performance and voltage retention as well as improved safety. This systematic study explores a material model combining Li-rich and high-Ni layered cathodes that is shown to be effective in creating a balance between mitigated voltage decay and high energy density.
Publisher Copyright: Copyright © 2020 American Chemical Society.
Keywords: gradient particles; ion exchange; Li-rich layered cathode; mitigated voltage decay